Sleep efficiency as a determinant of insulin sensitivity in overweight and obese adolescents. (September 2015) - Dorenbos, E.; Rijks, J. M.; Adam, T. C.; Westerterp‐Plantenga, M. S.; Vreugdenhil, A. C. E.
Abstract: Insulin resistance (IR) occurs in a transient manner during puberty. Obese adolescents may be at risk for persistent IR during puberty. The objective of the study is to review the literature on the association of the anthropometry and lifestyle characteristics with insulin sensitivity in overweight and obese adolescents, and include data from a new study. Relevant papers were selected and reviewed. In addition, 137 overweight and obese adolescents (42 male/95 female, age 14.4 ± 2.3 years, BMI z ‐score +3.3 ± 0.7, HOMA‐IR 3.4 ± 1.8) from the Centre for Overweight Adolescent and Children's Healthcare (MUMC+) were included in this study. Anthropometrics, Tanner stages, sleep characteristics, food intake behaviour and physical activity were determined, and possible associations with homeostasis model assessment of insulin resistance (HOMA‐IR) were tested. Results: Overweight and obese adolescents with unfavourable fat partitioning and family history of NIDDM are at risk for persistent IR. Overweight and obese adolescents from the new cohort showed a higher HOMA‐IR postpubertally. BMI z ‐score, age, pubertal stage and prepubertally total sleeping time (TST) and sleep efficiency (SE) were identified as significant contributors. Overweight and obese adolescents showed a persistently higher instead of transiently higher HOMA‐IR during puberty, associated with BMI z ‐score, age, pubertal stage and prepubertally less TST and SE.